A Qualitatively New Effect in Corporative Finance: Abnormal Dependence of Cost of Equity of Company on Leverage - Brusov, P.N.; Filatova, T.V.; Orekhova, N.P. (Journal of Reviews on Global Economics, 2013)
Qualitatively new effect in corporative finance is discovered: decreasing of cost of equity ke with leverage L. This effect, which is absent in perpetuity Modiglianiâ€“Miller limit, takes place under account of finite lifetime of the company at profit tax rate, which exceeds some value T*. At some ratios between cost of debt and cost of equity the discovered effect takes place at profit tax rate, existing in western countries and Russia. This provides the practical meaning of discussed effect. Its accounting is important at modification of tax low and can change the dividend policy of the company. In paper the complete and detailed investigation of discussed effect, discovered within Brusov â€“ Filatova â€“ Orekhova theory (BFO theory), has been done. It has been shown, that the absence of the effect at some particular set of parameters is connected to the fact, that in these cases T* exceeds 100% (profit tax rate is situated in â€nonâ€“ financialâ€ region).